2005
DOI: 10.1007/s11178-005-0344-2
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular 1,3-Dipolar Cycloaddition of Azomethine Ylides Generated from Ethoxycarbonylcarbenoids and Schiff Bases

Abstract: Decomposition of ethyl diazoacetate in the presence of copper, copper acetylacetonate, or copper trifluoroacetylacetonate and ethyl 4-[2-(R-imino)phenoxymethyl]-2-butenoate leads to formation of chromeno-[4,3-b]pyrrole-2,3-dicarboxylic acid derivatives. The reactions involve intermediate formation of azomethine ylides which undergo regio-and stereoselective intramolecular cycloaddition at the C=C bond to afford chromeno[4,3-b]pyrroles. The steric structure of the product depends on the configuration of interme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 17 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…With diazoacetophenone 2c , the only isolable product was pyrroline 5a , formed in modest yields (entry 10). Apparent dehydrogenation products of this sort were also obtained from the reaction of 2c with azetidines 1b , c (entries 11 and 12) . Variation of the azetidine exocyclic nitrogen substituent, replacing N -benzyl with N -pentyl or N -allyl, had little effect on the overall efficiency of the process.…”
Section: Resultsmentioning
confidence: 97%
“…With diazoacetophenone 2c , the only isolable product was pyrroline 5a , formed in modest yields (entry 10). Apparent dehydrogenation products of this sort were also obtained from the reaction of 2c with azetidines 1b , c (entries 11 and 12) . Variation of the azetidine exocyclic nitrogen substituent, replacing N -benzyl with N -pentyl or N -allyl, had little effect on the overall efficiency of the process.…”
Section: Resultsmentioning
confidence: 97%
“…Compound 4 (5.96 g, 94%) was obtained as a low melting solid. IR (film, cm À1 ): 2120, 1222; 1 H NMR (CDCl 3 ) 7.54e7.57 (1H, m, AreH), 7.28e7.32 (1H, m, AreH), 7.00e7.04 (2H, m, AreH), 5…”
Section: -(Dimethoxymethyl)-2-(prop-2-ynyloxy)benzene (4)mentioning
confidence: 99%
“…4 A similar approach involving the generation of azomethine ylides from ethoxycarbonylcarbenoids and Schiff bases of O-alkynyl salicylaldehydes is known. 5 On the other hand, it has been demonstrated that the reaction of imines derived from O-alkenyl salicylaldehydes and acid chlorides mediated by PhP(2-catechyl) leads to chromeno [4,3-b]pyrrole derivatives via intramolecular cycloaddition of phosphorus-containing 1,3-dipoles. 6 Despite the existing methods for the synthesis of chromeno [4,3b]pyrrole derivatives, there still is demand for strategies to achieve wider structural diversity.…”
Section: Introductionmentioning
confidence: 99%
“…Because of our research interest concerning the chemistry of azirines and the synthesis of nitrogenated heterocycles via reactions of diazo compounds with imines, ,,,, we envisioned the possibility of assembling a new heterocyclic system, 5-oxa-1-azabicyclo[4.1.0]­hept-3-ene 1 , by the reaction of azirines 2 with acylketenes 3 , according to the retrosynthetic sequence described in Scheme .…”
Section: Introductionmentioning
confidence: 99%